Trascendencia constitucional de las cláusulas de seguridad de los tbi celebrados por el Perú - Carnero Arroyo, Ena Rocío (2015)
In the present investigation bilateral investment treaties (BITs) signed by Peru, in order to answer the question about its impact on the fundamental principles of the Peruvian Constitution were made. Deductive method to study the incorporation of TBI in our legal system and to determine whether they are self-executing was used. Analysis and synthesis to study the terms of the 33 BITs signed by Peru and force was applied. The results allowed to verify that BITs are part of the international sources that our Constitution recognizes in article 55; that are integrated into our constitutional system automatically and constitutional law have hierarchy like any other treaty, except in the case of human rights treaties acquire via constitutional interpretation. It was also found that BITs are considered executive agreements, to be approved without the requirement of prior congressional approval and are the clauses of dispute resolution that authorizes the foreign investor access or the Center for the Settlement of Disputes concerning Investment Disputes (ICSID) under the ICSID Convention or to ad hoc arbitration of the United Nations Commission on International Trade Law (UNCITRAL impact on the principle of constitutional supremacy and other fundamental principles.